Research on Distribution Automation Based on Power Supply Reliability - Du, Shuai (Manufacturing Technology Journal, 2019)
The development of economy can not be separated from sufficient energy supply. With the progress of technology, the distribution network gradually expands the capacity and transportation, but also brings security risks. The distribution automation system can effectively manage the power grid faults. This paper briefly introduced the calculation model of the economic cost and the reliability rate of the distribution automation, and then the assembly scheme of the distribution terminal was optimized by using the improved binary particle swarm optimization (PSO) algorithm. Next, the simulation analysis of the distribution terminal distribution on a 10KV main feeder line in Xuanwu District of Nanjing city was carried out in MATLAB software. The results showed that the improved binary PSO algorithm could optimize the assembly scheme of remote metering and remote signalling and the assembly scheme of remote metering, remote signalling and remote control rapidly; the hybrid assembly scheme needed a little more time; the power supply reliability rate of the optimized three terminal assembly schemes was over 99%; the hybrid assembly scheme had higher power supply reliability rate and the lowest economic cost.
Keywords: Distribution Automation; Economic Cost; Power Supply Reliability; Particle Swarm Optimization